Forage quality on family farms in Croatia hay quality on family farms - Marina Vranić; Mladen Knežević; Goran Perčulija; Josip Leto; Krešimir Bošnjak; Ivana Rupić (Mljekarstvo)
The aim of the applied research project: “Forage evaluation by NIR spectroscopy” was to monitor the nutritive value of grass silage, corn silage and hay on family farms in Croatia over 6-month feeding (from November 2003 to May 2004). In this paper the nutritive value of hay on 18 dairy family farms from 5 counties was investigated.Extension service staff recommended dairy nutrition based on monthly silage analysis by NIRS instrument (Foss, Model 6500).Dry matter (DM) content was determined by wet chemistry while Scottish calibration models were applied and following parameters are estimated: crude protein (CP), neutral detergent fiber (NDF), metabolizable energy (ME), water-soluble carbohydrates (WSC) and organic matter digestibility in DM (D-value). The average results show desirable DM content (873.75 g kg-1), high NDF (677.56 g kg-1DM), but low WSC (77.46 g kg-1 DM), CP (65.74 g kg-1 DM), ME (8.64 MJ kg-1 DM) and D-value (57.67%). Great variations were observed for CP (40-209 g kg-1 DM), ME (6-12 MJ kg-1DM), UTV (20-203 g kg-1 DM) and D-value (40-80%). Statistically significant differences (P<0.05) were recorded for DM (P<0.05) and WSC (P<0.05).